BRIDGING DA AND ETHNOMETHODOLOGICALLY DA - Indri Christina (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
The aims of this paper try to discuss and present various theoretical perspectives of discursive phenomena, in specific the different research techniques widely known as, as well as the theories. Having presented the main assumptions of the approach the paper, then discusses and analyze discursive interactions’ phenomena, technologically mediated interaction or face-to-face. By concentrating on the pragmatic aspects of discourse, an ethnomethodologically approach of discourse analysis, this paper may contribute important ideas and information in media interaction studies.